2016
DOI: 10.3390/d9010001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Growth of Juvenile Crown-of-Thorns Starfish on the Northern Great Barrier Reef

Abstract: Abstract:The corallivorous crown-of-thorns starfish (Acanthaster spp.) is a major cause of coral mortality on Indo-Pacific reefs. Despite considerable research into the biology of crown-of-thorns starfish, our understanding of the early post-settlement life stage has been hindered by the small size and cryptic nature of recently settled individuals. Most growth rates are derived from either laboratory studies or field studies conducted in Fiji and Japan. The Great Barrier Reef (GBR) is currently experiencing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 30 publications
(58 reference statements)
2
36
0
Order By: Relevance
“…Observations of newly settled A. cf. solaris in the field (Yokochi and Ogura 1987;Zann et al 1987;Wilmes et al 2016), have revealed a strong and consistent association with CCA, which is expected given that newly settled starfish feed almost exclusively on coralline algae (Yamaguchi 1973;Lucas 1984;Zann et al 1987).Settlement experiments conducted under laboratory conditions (Yamaguchi 1973;Johnson et al 1991;Uthicke et al 2015b;Wolfe et al 2015a;Kamya et al 2016;Pratchett et al 2017b) reaffirm that CCA is important for inducing CoTS settlement. When examined microscopically, the surface of CCA is roughly textured -this finescale topographic complexity can provide a tactile stimulus for larvae to settle (Lucas 1974).…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Observations of newly settled A. cf. solaris in the field (Yokochi and Ogura 1987;Zann et al 1987;Wilmes et al 2016), have revealed a strong and consistent association with CCA, which is expected given that newly settled starfish feed almost exclusively on coralline algae (Yamaguchi 1973;Lucas 1984;Zann et al 1987).Settlement experiments conducted under laboratory conditions (Yamaguchi 1973;Johnson et al 1991;Uthicke et al 2015b;Wolfe et al 2015a;Kamya et al 2016;Pratchett et al 2017b) reaffirm that CCA is important for inducing CoTS settlement. When examined microscopically, the surface of CCA is roughly textured -this finescale topographic complexity can provide a tactile stimulus for larvae to settle (Lucas 1974).…”
mentioning
confidence: 83%
“…However, collections were mainly intended to inform growth models (see section 2.16) and so limited information was collected regarding the specific habitat conditions and exact densities. Despite limited success in the past (Doherty and Davidson 1988;Johnson et al 1992), current work by Wilmes et al (2016) demonstrates that 0+ year juveniles can be effectively sampled in the field, and much more sampling is required to establish variation in rates of settlement across different reef areas, depths and habitats. There are also methods available for measuring settlement rates of Acanthaster spp., using settlement collectors constructed from high surface area plastic biospheres (Keesing et al 1993), which will be important to differentiate where larvae settle versus where they survive and are actually recorded several months after settlement (sections 2.9-2.11).…”
Section: Question 11 and 13 (Larvae And Juveniles) -Where Do Larvae Smentioning
confidence: 99%
See 3 more Smart Citations